Reputation Formation for Reliable Reporting: An Experimental Investigation. - King, Ronald R. (The Accounting Review, 1996)
Studies the extent to which corporate information senders develop reputations for truthful reporting. Reputation formation; Incentives for voluntary dissemination of information; Buyers' forecasting and bidding strategies.